A Perspective on IL-7Rα Deficient T−B+NK+ Severe Combined Immunodeficiency. Issue 3 (March 2015) - Xinghan, Kristy Fu; Harkensee, Christian
Abstract : The management of patients with IL-7Rα deficient, T−B+NK+ severe combined immunodeficiency (SCID) is a challenge in absence of adequate diagnostic and treatment modalities. An infant diagnosed as SCID at 6 months of age, who received only supportive treatment is described. We present a different perspective of SCID that is managed in a low-middle income country with lack of resources for definitive therapy.